Impact of Student Support Services on Student Learning Satisfaction at Qingdao Preschool Education College - cai, le; Kamonrojsiri, Pattaroj (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The research is quantitative research. The purpose of this research is to study the impact of student support services on learning satisfaction at Qingdao Preschool Education College using quantitative methods. A validated questionnaire (Cronbach’s α = .873) was administered to 362 students, with data analyzed via descriptive statistics, correlation, and multiple regression. Key findings reveal: Students perceived support services neutrally overall (M range 3.31-3.49). Learning satisfaction components were also rated neutrally (M range 3.29-3.34). Correlation analysis showed significant positive relationships between learning satisfaction and both health support (r = .35, p < .01) and personal/career development services (r = .42, p < .01). Crucially, the multiple regression analysis confirmed that Health Support Services (β = 0.291, p < 0.001) and Personal and Career Development Services (β = 0.391, p < 0.001) were significant positive predictors of overall learning satisfaction, with the latter having the strongest effect. In contrast, Academic Support Services (p = .995) and Financial Support Services (p = .488) did not demonstrate a significant predictive impact within this model. These results underscore the critical role of wellness and career-readiness support in this vocational setting. The study recommends prioritizing career development initiatives and strengthening mental health resources to enhance student learning satisfaction.